Electromagnetic Scattering in a Two-Layered Medium (Communications in Mathematical Research, 2021)
The object of this paper is to investigate the three-dimensional electromagnetic scattering problems in a two-layered background medium. These problemshave an important application in today’s technology, such as to detect objects thatare buried in soil. Here, we model both the exterior impedance problem and theinhomogeneous medium problem in $\boldsymbol{R}^3$. We establish uniqueness and existence forthe solution of the two scattering problems, respectively.
Keywords: electromagnetic; scattering problem; layered medium; integral equation; uniqueness and existence; Green function.